Correlación entre la confiabilidad y validez de las pericias psicológica y médico legal en la investigación preliminar del delito de violación de la libertad sexual - Linares Calderón, Juan Nelson (2012)
The purpose of this research is to analyze the relationship between indices of reliability and validity of psychological skills and medical expertise - legal of the alleged victims of crimes of violation of sexual freedom in the process of preliminary investigation of the Provincial Criminal Prosecutor Ministry of Public corporate district of Trujillo in 2007 and 2008. The methodology was applied analytical method - synthetic technique was used as survey instruments and two questionnaires. Also used the technique of analysis of documents. The results showed no relation between indices of reliability and validity of skills, it was accepted that both skills are relevant probative evidence in the preliminary investigation. It was also shown that the values according to Wilcoxon, the average reliability and validity of forensic expertise is greater than the average rate of reliability and validity of psychological expertise. The findings led to the need to further clarify, organize and link the psychological and legal expertise.